Unpacking Functions and Meanings of Prefixes Inter- and Intra- to Enhance Learners’ Morphological Awareness - Trifosa, Maria; Bram, Barli (IKIP Siliwangi, 2026)
Morphological awareness is crucial in EFL vocabulary acquisition, particularly in understanding complex word formations. This research analyzes the morphological behavior of prefixes inter- and intra- to determine how their meanings and grammatical roles shift across different word classes. Employing a qualitative descriptive approach, the researchers collected 345 lexical entries (183 for inter- and 162 for intra-) from the Oxford English Dictionary. The analysis focused on word class changes and semantic formations. The results show distinct characteristics: inter- exhibits broader morphological flexibility, forming verbs, nouns, and adjectives that describe reciprocal relationships, spatial distance, and social relations. Conversely, intra- demonstrates structural consistency, predominantly forming technical adjectives referring to internal locations within scientific contexts. These findings highlight the significant role of prefixes in vocabulary enrichment and the necessity of understanding word class nuances. Practically, this study suggests that teaching strategies should differentiate between the communicative nature of inter- and the technical specificity of intra-. This research contributes a morphology-based framework for teaching English vocabulary in EFL contexts.